Performance evaluation and damage assessment of historical Yusuf Ziya Pasha Mosque after February 6, 2023 Kahramanmaras earthquakes - Onat, Onur; Deniz, Faruk; Ozmen, Alper; Ozdemir, Engin; Sayin, Erkut (Elsevier Science Inc, 2023)
Historical masonry heritages are severely affected by the February 6, 2023, Kahramanmaras, earthquakes. The recorded earthquake peak ground accelerations (PGA) are 2.05 g and 0.67 g for Pazarcik and Elbistan earth-quakes at the epicenter, respectively. However, there is not any recorded PGA data related to Kahramanmaras, earthquakes in Malatya. At this point, the current study aims to propose a methodology to estimate the possible resisted load of historical Yusuf Pasha Mosque in Malatya and possible PGA for Malatya by assessing the per-formance located in Malatya city center, which is far from the epicenter of Pazarcik earthquake, which is 162 km, and Elbistan earthquake, which is 100 km, using propagated cracks. After these earthquakes, local damages were registered at the Yusuf Ziya Pasha Mosque. The main prayer hall of the mosque and a tomb were constructed in 1792. Three types of materials were used for the mosque: riyolit tuff, sandy tuff for walls, and timber for the roof. The dimensions of the main hall of the mosque are 17.50 m x 12.53 m. Additionally, there is a small tomb located adjacent to the mosque with dimensions of 7.61 m by 4.46 m. First of all, dynamic identification is conducted, and then a numerical model is generated. Material properties were calculated using non-destructive testing methods. The mosque and the tomb are modeled together. The numerical model is calibrated on the basis of the extracted dynamic parameters. Then, nonlinear time history analyses were performed on the model using eight earthquake records. Three of the used seismic records were international, namely the 1995 Kobe, 1986 Chalfant Valley, and 2010 New Zelland Darfield earthquakes. In addition, five national earthquake records are used for the nonlinear dynamic analyses, namely the 2003 Bingo center dot l, 2011 Van-Ercis,, 2020 Elazig-Sivrice, 2023 Kahramanmaras, Pazarcik, and Elbistan earthquakes. Related graphs were tabulated, and crack propagations of the numerical model were compared to damaged mosques.
Keywords: Kahramanmaras , earthquakes; Historical masonry mosques; Nonlinear time history analyses; Yusuf Ziya Pasha Mosque; Malatya